2022
DOI: 10.1161/jaha.121.025984
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index in Adolescence and Long‐Term Risk of Early Incident Atrial Fibrillation and Subsequent Mortality, Heart Failure, and Ischemic Stroke

Abstract: Background We sought to determine the role of obesity in adolescent men on development of atrial fibrillation (AF) and subsequent associated clinical outcomes in subjects diagnosed with AF. Methods and Results We conducted a nationwide, register‐based, cohort study of 1 704 467 men (mean age, 18.3±0.75 years) enrolled in compulsory military service in Sweden from 1969 through 2005. Height and weight, blood pressure, fitness, muscle strength, intelligence quotient, and medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(54 reference statements)
2
5
0
Order By: Relevance
“…Our study reiterates the well-established association between elevated BMI and increased stroke risk, corroborating previous research findings [ 3 , 4 ]. Obesity, as indicated by BMI, is recognized as a significant and modifiable risk factor for stroke [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study reiterates the well-established association between elevated BMI and increased stroke risk, corroborating previous research findings [ 3 , 4 ]. Obesity, as indicated by BMI, is recognized as a significant and modifiable risk factor for stroke [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study reiterates the well-established association between elevated BMI and increased stroke risk, corroborating previous research findings [ 3 , 4 ]. Obesity, as indicated by BMI, is recognized as a significant and modifiable risk factor for stroke [ 3 , 4 ]. Particularly abdominal or visceral obesity, is associated with a host of metabolic abnormalities, including insulin resistance, dyslipidemia, and inflammation [ 27 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There are multiple lines of evidence linking obesity and AF. Numerous epidemiological studies have shown that obesity is associated with new-onset AF even after adjustment for other comorbidities associated with obesity [ 24 , 25 , 26 ]. A meta-analysis of 51 studies with over 600,000 individuals by Wong et al showed a 29% greater risk of overall incident AF and a 10% greater risk of postoperative AF for each 5-unit increase in BMI [ 19 , 27 ].…”
Section: Epidemiology Of Obesity and Afmentioning
confidence: 99%